Model sensitivity of the Weddell and Ross seas, Antarctica, to vertical mixing and freshwater forcing. (October 2015) - Kjellsson, Joakim; Holland, Paul R.; Marshall, Gareth J.; Mathiot, Pierre; Aksenov, Yevgeny; Coward, Andrew C.; Bacon, Sheldon; Megann, Alex P.; Ridley, Jeff
Highlights: Convection in Weddell and Ross seas sensitive to mixing, freshwater flux and initial sea ice cover. 0.2 PSU salinity difference across pycnocline ∼30% bias in freshwater flux can erode stratification in a decade. Sensitive to magnitude and horizontal distribution of runoff Vertical mixing, freshwater flux, and initial sea ice cover must be considered together Graphical abstract: Abstract: We examine the sensitivity of the Weddell and Ross seas to vertical mixing and surface freshwater forcing using an ocean–sea ice model. The high latitude Southern Ocean is very weakly stratified, with a winter salinity difference across the pycnocline of only ∼0.2 PSU. We find that insufficient vertical mixing, freshwater supply from the Antarctic Ice Sheet, or initial sea ice causes a high salinity bias in the mixed layer which erodes the stratification and causes excessive deep convection. This leads to vertical homogenisation of the Weddell and Ross seas, opening of polynyas in the sea ice and unrealistic spin-up of the subpolar gyres and Antarctic Circumpolar Current. The model freshwater budget shows that a ∼30% error in any component can destratify the ocean in about a decade. We find that freshwater forcing in the model should be sufficient along the Antarctic coastline to balance a salinity bias caused by dense coastal water that is unable to sink to the deep ocean. We also show that a low initial sea ice area introduces a salinity bias in the marginal ice zone. We demonstrate that vertical mixing, freshwater forcing and initial sea ice conditions need to be constrained simultaneously to reproduce the Southern Ocean hydrography, circulation and sea ice in a model. As an example, insufficient vertical mixing will cause excessive convection in the Weddell and Ross seas even in the presence of large surface freshwater forcing and initial sea ice cover.